The Monterey Vineyard, Cabernet Sauvignon, 1979 - Monterey Vineyard::::::::: (1979)
Wine label for a 1979 Cabernet Sauvignon sourced from grapes in San Luis Obispo County, and produced and bottled by The Monterey Vineyard in Gonzales, CA as a French Camp Vineyard Special Selection.